Stakeholder Participation In The Implementation Of Local Agenda 21 In Malaysia - Mohamed Osman, Mariana (2008)

(untitled)
Central to this study is the subject of community participation and local governance in Malaysia. It is acknowledged that the community and local authority play an important role in the local decision making process. Stakeholder participation has become an important part of the decision making process. It can empower and significantly influence the decision making process as well as the project design. How effective has participation been historically? Does it actually influence the decision making process in Local Agenda 21 (LA21)? It has been noted that participation practices have increased over the last three decades and is now practised in the planning and development process. However, the constant debates over stakeholder participation and citizen control have not resulted in the ability to identify its real issues and problems. Planning and participation of stakeholder at local level is the process of incorporating into the plan consideration of stakeholder needs, preferences and values attributable to each proposal before the decision making body. The determination of effective planning and decision in LA21 takes into account diverse perspectives and impact allowing the decision makers the opportunity to find solutions and empower stakeholder and local citizen in the LA21 process. This thesis examines the roles of the stakeholders i.e. community residents, local authority staffs and community organizations in LA21 process in Malaysia. The objectives of this research are to identify the level of participation of local authorities in LA21 and to investigate factors influencing the participation of the local authorities in LA21 in Malaysia. Furthermore, the research examines the way in which the participatory principles of LA21 are being carried out in Malaysia, using Petaling Jaya as a case study. The research uses a model of public participation to analyse the Petaling Jaya case study showing the level of participation among community in the LA21 process. The research uses several methods to collect the data which includes self administered questionnaire, interviews and participated observation. The investigation includes an examination of the problems faced by the stakeholder in the participation process of LA21 and the reasons for the low level of adoption of LA21 by local authorities in Malaysia. However, as this research will illustrate through survey and case study analysis, there are several factors and limitations contributing to the success of stakeholder participation in Local agenda 21 process. By highlighting these factors and limitations, the researcher’s goal is to mobilize research and policy efforts to overcome those limitations and to foster widespread stakeholder participation in the implementation of LA21 among local authorities in Malaysia.The results show that there is low level of participation among local authorities in LA21 in Malaysia. In the case study of Petaling Jaya, the level of participation among community is also low ranging from ‘non-participation’ to ‘tokenism’ level and not at the ‘partnership’ level as it should be in a LA21 process. In the case study it was found that the local authority try to emphasise a listening and open approach to decisionmaking process, but despite their commitment to participation, there has been limited success in securing widespread involvement and trust of people into the process. Key issues to emerge are the importance of the commitment of key individual and politicians, the readiness of the authorities to the outcomes of the participatory methods (responsive, transparent and consensus decision) and the need for participation to be an ongoing commitment by the authorities themselves rather than just one off exercise. The implications are that change is needed in the way local authorities relate to the communities they serve, but this will place considerable demand on already stretched local authority resource, particularly where positive action is needed to build capacity.